Post-earthquake fire assessment of buildings : evaluation framework - Elhami-Khorasani, Negar; Braxtan, Nicole; Carlton, Aerik; Coar, Maxwell; Dalton, John; Farshadmanesh, Pegah; Kamath, Praveen; Ketabdar, Mehrshad; LaMalva, Kevin; Memari, Mehrdad (American Society of Civil Engineers, 2022)
This book provides background for the analysis, design, and assessment of building structural systems under fire following earthquakes.